Turistification in Lisbon. Colección de dibujos etnográficos - Ramos, M. (Revista Andaluza de Antropología, 2018)
Accompanying sketch collection of the article "Suddenly last summer: how the tourist tsunami hit Lisbon", by Daniel Malet and Manuel João Ramos, in the same issue of the journal Revista Andaluza de Antropología (2018, 15, pp 47-73), DOI: 10.12795/RAA.2018.15.03